2003
DOI: 10.1097/00006676-200308000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Exocrine Pancreatic Cancer, Cigarette Smoking, and Diabetes Mellitus: A Case-Control Study in Northern Italy

Abstract: The role of cigarette smoking and diabetes mellitus as risk factors for exocrine pancreatic cancer (PC) was investigated in a hospital based case-control study. Current smokers were at increased risk for PC (OR = 2.36, 95% CI 1.53-3.63): the magnitude of the risk was related to the lifetime amount of smoking (chi2(trend) = 17.00; P < 0.0001). Among former smokers, after 15 years from ceasing smoking, the risk for PC dropped to the level of a lifetime non-smoker, whichever the lifetime smoking amount. Diabetes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
64
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(73 citation statements)
references
References 29 publications
7
64
0
2
Order By: Relevance
“…However, the strongest associations were observed among regular smokers and among women, consistent with previous findings. [3][4][5] We also observed that the most important parameter of smoking that affected pancreatic cancer risk was the duration of regular smoking, although risk also increased with the number of cigarettes smoked per day. The finding that the risk of pancreatic cancer was associated more strongly with the duration than with the intensity of smoking may reflect in part the accuracy with which these 2 parameters are measured.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, the strongest associations were observed among regular smokers and among women, consistent with previous findings. [3][4][5] We also observed that the most important parameter of smoking that affected pancreatic cancer risk was the duration of regular smoking, although risk also increased with the number of cigarettes smoked per day. The finding that the risk of pancreatic cancer was associated more strongly with the duration than with the intensity of smoking may reflect in part the accuracy with which these 2 parameters are measured.…”
Section: Discussionmentioning
confidence: 96%
“…1 It has been demonstrated that cigarette smoking is responsible for approximately 25% of pancreatic cancer cases. [2][3][4][5] Other factors, such as diet, history of chronic pancreatitis, diabetes, family history of pancreatic cancer, and some hereditary conditions, also may contribute to the development of this deadly disease. [6][7][8][9][10][11] Smoking prevalence in the United States has declined since 1997; however, despite the overwhelming evidence of the harmful effects of smoking, almost 22% of adults in the United States still smoked cigarettes in 2003.…”
mentioning
confidence: 99%
“…As far as we know, no published cohort data on smoking and pancreatic cancer risk are available for Central or Southern European countries. Six primarily hospital-based case-control studies that were conducted in Greece, 23 Italy [24][25][26][27] and Spain 28 reported conflicting results. Three studies 23,24,26 showed an increased pancreatic cancer risk for current smokers, whereas the other three found no association.…”
Section: Discussionmentioning
confidence: 99%
“…Six primarily hospital-based case-control studies that were conducted in Greece, 23 Italy [24][25][26][27] and Spain 28 reported conflicting results. Three studies 23,24,26 showed an increased pancreatic cancer risk for current smokers, whereas the other three found no association. 25,27,28 The increased pancreatic cancer risk we observed among current smokers in Northern and Central, but not in Southern European countries, may be explained by small numbers or by differences in smoking practices.…”
Section: Discussionmentioning
confidence: 99%
“…In an analysis requiring a 5-year duration of diabetes resulted in similar results, with RR of 2.0 (95% CI 1.2-3.2) in 11 epidemiologic studies [ Table 2]. In a hospital based case-control study, Bonelli et al have demonstrated that the risk of pancreatic cancer was increased by 6.2 fold in patients with diabetes, which necessitated insulin therapy for greater than 5 years (Bonelli et al, 2003). Jamal and colleagues further supported these findings with their large population-based case-control study of 1,172,496 patients, by demonstrating that occurrence of pancreatic cancer was increased by threefold in DM patients compared to controls (frequency of pancreatic cancer in DM subjects 0.9% compared to control subjects 0.3% with OR:3.22, 95% CI: 3.03-3.42) (Jamal et al, 2009) [Table 2].…”
Section: Epidemiologic Studiesmentioning
confidence: 76%